Governança Desgovernada: uma história econômica do Plano Real a partir de sua incoerência teórica (1994-1999) - Victor Garcia Miranda (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
This paper aims to analyze the operational process of the Plano Real and its effects measured in the Brazilian economy and politics at the time of existence of the nominal anchor based on the parity exchange rate between the national currency and the dollar (1994-1999). It is interpreted as the Plano Real project that sought the stability of the economy by combat for hyperinflation and who was also involved in a specific cyclical arrangement, which requires historical interpretation – not only technical and economic interpretation. Assuming that there was influence of the neoclassical theory of macroeconomic choice with instruments and objectives of Robert A. Mundell (1932), this text seeks the historical manifestation of economic and political effects to thePlano Real and if there was agreement which was written by a theorist who influenced the formation of the "fathers of the Real" and the reality of the currency board experience developed in Brazil since 1994. Thisresearch indicate that there was deep inconsistency between the presumptuous theorizing Mundell and effects historically found, dismounting the conception of infallibility of neoclassical theories. Contrariwise, such effects caused deepening of the country's dependence on condition against the backdrop of international capitalism that moment, through the deepening crisis in the payment balace and the financialization of the Union public deficit.